Pengaruh Lama Pemanasan Bakteriosin dari Isolat Bal PR.6.10.5 dan PR.6.15.2 Terhadap Daya Hambat Pertumbuhan Staphylococcus aureus ATCC 25923 dan Escherichia coli ATCC 8739 - Sihombing, Sarah Yohana; Antara, Nyoman Semadi; Triani, Gusti Ayu Lani (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2021)
After being heated at 100o Celcius, the bacteriocins from the pickled LAB of tabah bamboo shoots hypothetically predicted to be able to inhibit the growth of pathogenic bacteria, especially S. aureus ATCC 25923 and E. coli ATCC 8739. The LAB isolates thus were heated at a temperature of 100o C for various of 5, 10, 15 minutes heating time and subsequently measured by regression and correlation analysis of its influence towards the inhibition of the growth of S. aureus ATCC 25923 and E. coli ATCC 8739 bacterias. This study shows the variations of heating time at a temperature of 100°C resulted with of inhibition zone’s diameter formation (mm), activity values (mm2/ml), and the effects (r dan R2) of these two bacteriocins towards its inhibition on the bacterias. Keywords: Lactic acid bacteria (LAB), bacteriocin, Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 8739, heating time.